Un soplo de vida : pulsaciones - Lispector, Clarice (Biblioteca Clarice Lispector, 2016)
At her death, a mountain of fragments remained to be "structured" by Olga Borelli. These fragments form a dialogue between a god-like author who infuses the breath of life into his creation: the speaking, breathing, dying creation herself, Angela Pralini. The work's almost occult appeal arises from the perception that if Angela dies, Clarice will have to die as well. And she did.